A biomechanical analysis of plate fixation using unicortical and bicortical screws in transverse metacarpal fracture models subjected to 4-point bending and dynamical bending test. Issue 27 (July 2017) - Liodaki, Eirini; Wendlandt, Robert; Waizner, Klaus; Schopp, Brigitte E.; Mailänder, Peter; Stang, Felix
Abstract : Abstract: In the published literature there are controversial data to the biomechanical stability of monocortical comparing to the bicortical fixation of metacarpal fractures. The aim of this study was to compare the biomechanical stability of monocortical and bicortical locking osteosynthesis in quasi-static and dynamic 4-point bending tests of composite third metacarpal bone (4th Gen third metacarpal, Sawbones, Malmö, Sweden) fixed with 7-hole locking plate (XXS System, Biotech-Ortho, Wright, Memphis, TN). The tests to determine quasi-static yield and bending strength as well as fatigue strength were conducted in 4 groups of 10 samples after creating standardized mid-shaft transverse osteotomies using a diamont belt grinder (0.3 mm saw blade). The force applied was the dorsal apex loading, similar to the forces applied to metacarpals during normal finger flexion and extension. In the quasi-static testing, no plate breakage was observed in each group. All metacarpals broke at their thinnest part. The average bending strength of the bicortical samples (10.54 ± 0.998 Nm) was significantly higher comparing to the monocortical samples (8.57 ± 0.894 Nm) ( P < .001). In the dynamic loading test, all constructs (8 monocortical samples and 7 bicortical) that failed broke at the osteotomy site and the average fatigue strength did not differ in both groups. Consequently, a unicortical plating method may provide adequate strength and stability to metacarpal fractures based on the results of the cyclical loading representative of in vivo loading.